COVID-19 Health Protocol Training on the Competence of Village Community Leaders - Anatolia Karmelita Doondori; Pius Kopong Tokan; Irwan Budiana (Science Midwifery, 2022)
Indonesia is a country with a fairly high rate of COVID-19 transmission. There are various efforts made by the government to control the transmission of COVID-19. These efforts still require support and countermeasures such as maximizing the involvement of community leaders. This study aims to identify the competence of community leaders which includes knowledge, skills and attitudes and then analyze the effect of COVID-19 health protocol training on the competence of community leaders. This research is a quantitative study with a quasi-expreminent design with a one group pre-test-post-test design. There was no comparison group (control) but the first observation (pre-test) was carried out before giving the intervention and a post-test was carried out. The intervention carried out was training on COVID-19 health protocols. The population in this study were all community leaders who live in the village of Gheo Goma and the sampling in this study used a purposive sampling technique. The instruments used in this study were questionnaires and the SOP for the COVD-19 health protocol. Data analysis used dependent t-test (paired t-test). The results of the analysis showed that the p value of the knowledge variable was 0.0851, the attitude variable was 0.415 and the skill variable was 0.234 (>0.05). There is no difference in the competence of community leaders in preventing or managing non-natural disasters Covid-19 before and after being given COVID-19 health protocol training.